Flowering type and morphological diversity of Bido coconut from Morotai Island District, Indonesia - SUKMAWATI MAWARDI; MUHAMMAD ROIYAN ROMADHON; RAHMA RAHMA; ISMAIL MASKROMO; DINY DINARTI; SUDARSONO SUDARSONO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Mawardi S, Romadhon MR, Rahma, Maskromo I, Dinarti D, Sudarsono. 2023. Flowering type and morphological diversity of Bido coconut from Morotai Island District, Indonesia. Biodiversitas 24: 1473-1481. In general, coconuts are divided into Tall and Dwarf types. Dwarf coconut is early bearing and has a short trunk, while Tall coconut yields high-quality copra and has a large fruit size. Furthermore, Bido-Tall coconut is an early bearing with a short trunk, medium size fruit, and high-quality copra. This research aims to evaluate Bido coconut population variations and study the flowering types of Bido and other coconut types in the research locations. Morphological and flowering type observation was conducted for Bido Tall, Local Tall, Local Dwarf, and Bido Tall outcrossing progenies at Bido Village, North Maluku, Indonesia. Flowering-type observations were carried out on three successive inflorescences. The Bido Tall, Dwarf, and the Bido Tall outcrossing progenies exhibited natural autogamy pollination, while the Local Tall coconut was semi-autogamy. The Principal Component Analysis (PCA) results indicated that the stem girth at 20 cm and 150 cm above ground, the internode length, the leaf numbers, the fruit color, and the fruit numbers cumulatively contributed to 68.80% of the observed coconut variabilities. Most Bido Tall coconut individuals were clustered separately from the existing local Tall and Dwarf coconuts. However, the clustering analysis showed average similarity among Bido Tall, the Local Tall, and Dwarf coconuts are still above 70%. The similarity coefficient among the Bido Tall coconut, the Bido Tall outcrossing progenies (natural hybrids), and the Local Tall was higher than among Bido Tall to the Local Dwarf coconuts.